Analisis Keuntungan Dan Analisis Keuntungan Dan Strategi Pengembangan Usaha Ayam Buras Unggul Varietas Jowo Super (JOPER) Di Kabupaten Jember - Eko Andris Widayanto; Syamsul Hadi; Saptya Prawitasari (STIE Mandala Jember, 2019)
This study aims to determine the profitability of domestic chicken business in Jember Regency, to find out the factors that influence the profitability of chicken farming in Jember Regency, determine the development strategy domestic chicken in Jember Regency. This researche used survey method. The research was conducted in 3 (three) Subdistricts namely Bangsalsari, Umbulsari, and Gumukmas Subdistricts, in Jember Regency. The data used in this researche include primary data and secondary data. The data is done qualitatively and quantitatively. The analysis used is profit analysis, multiple regression analysis and SWOT analysis. This researche concludes that (1) Wild Chicken Jowo Super (Joper) Business in Jember Regency is profitable with an average revenue gain of Rp. 9,749,038 per production process, and the total production costs are Rp. 9,082,346 per production process. The average business profit rate of Buras Joper Chicken in Kabupaten Jember is IDR 666,693 / production process / 404 heads. (2) Business Benefits of Burst Joper Chicken are influenced by 5 independent variables namely price (X1), production (X2), cost of production facilities (X3), labor costs (X4), and other costs (X5) with a positive relationship and significant at the real level of five percent. This is indicated by the results of the calculated F test greater than F table at the real level of 99%. Simultaneously the factors have a significant effect on profits including price, production, production facilities, labor costs and other costs. But partially significant factors include the price of output and production, while the ones that are not significant include the costs of means of production, labor costs, and other costs. (3) Based on the results of the SWOT Analysis, the Buras Chicken Business in Jember Regency is in position / quadrant I (Growth / Aggressive / progressive). This position signifies a strong and potential business, meaning that the business is carried out in prime condition. So that it is truly possible to continue to expand, increase growth and achieve maximum progress.